Learning obstacle materi lingkaran ditinjau dari diferensiasi kesiapan belajar - Nurfauziah, Puji; Hakim, Fahril; Maya, Rippi (IKIP Siliwangi, 2025)
Differentiated learning is learning that prioritizes and facilitates student needs according to student characteristics, one of which is learning readiness, which consists of groups ready for challenges, understanding concepts and repeated concepts. From these three groups, it will be analyzed how learning obstacles occur in analyzing the circle concept. This research is a qualitative descriptive study with 15 research subjects. Based on the results of data analysis, it can be concluded that the group of students who understand the concept and repeat the concept experience epistemological obstacles in understanding the relationship between the central angle and the circumferential angle, analyzing the area of a circle, analyzing the elements of a circle, and analyzing the relationship between the central angle and the area of the circle. Apart from that, students experience difficulty in representing the problems given because students are unable to find information and instructions from the questions given.